Association of ambulatory blood pressure monitoring with renal outcome in patients with chronic kidney disease - Hyung Eun Son; Ji Young Ryu; Suryeong Go; Youngjin Yi; Kipyo Kim; Yoon Kyu Oh; Kook-Hwan Oh; Ho Jun Chin (The Korean Society of Nephrology, 2020)
Background : : The significance of ambulatory blood pressure (ABP) in Korean patients with chronic kidney disease (CKD) in relation to renal outcome or death remains unclear. We investigated the role of ABP in predicting end-stage renal disease or death in patients with CKD. Methods : : We enrolled 387 patients with hypertension and CKD who underwent ABP monitoring and were followed for 1 year. Data on clinical parameters and outcomes from August 2014 to May 2018 were retrospectively collected. The composite endpoint was end-stage renal disease or death. Patients were grouped according to the mean ABP. Results : : There were 66 endpoint events, 52 end-stage renal disease cases, and 15 mortalities. Among all patients, one developed end-stage renal disease and died. Mean ABP in the systolic and diastolic phases were risk factors for the development of composite outcome with hazard ratios of 1.03 (95% confidence interval [CI], 1.01-1.04; P < 0.001) and 1.04 (95% CI, 1.02-1.07; P = 0.001) for every 1 mmHg increase in BP, respectively. Patients with mean ABP between 125/75 and 130/80 mmHg had a 2.56-fold higher risk for the development of composite outcome (95% CI, 0.72-9.12; P = 0.147) as compared to those with mean ABP ≤ 125/75 mmHg. Patients with mean ABP ≥ 130/80 mmHg had a 4.79-fold higher risk (95% CI, 1.68-13.70; P = 0.003) compared to those with mean ABP ≤ 125/75 mmHg. Office blood pressure (OBP) was not a risk factor for the composite outcome when adjusted for covariates. Conclusion : : In contrast to OBP, ABP was a significant risk factor for end-stage renal disease or death in CKD patients.